Pelatihan Pembuatan Buket Snack Sebagai Alternatif Ide Usaha Di Pasar Johar Kota Semarang - Nevis Ari Pratama; Daffa Rizki Nurwahid; Padmasiwi Khoirina Anjali; Novita Indriyanti; Novita Rahmawati (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
Through Training on Making Snack Bouquet as an Alternative Business Idea, this activity seeks to teach one of the alternative business ideas that may be done by everyone from various backgrounds. The general public's ignorance of flower bouquets makes it challenging for business players to identify their target market, as teens continue to use food bouquets as presents for specific individuals. In order for the participants in this training to use the snack bouquet business as a reference business idea in the future, it seeks to provide information about the making process and the materials required to establish one. Both theoretical and practical methods are employed in this training.